Characterising the regulatory network of MYB26 during anther dehiscence - Mo, Rui (2017)
Pollen development and release involves a number of important stages, which govern the success of fertilisation and thus indirectly crop yields. The secondary cell wall in the anther plays a pivotal role in anther dehiscence by offering mechanical strength required for opening and pollen release (Wilson et al. 2011). MYB26/MALE STERILE35(MS35) is a key regulator of the secondary thickening development in anther, mutation of this gene results in a failure of anther dehiscence and functional male sterility (Steiner-Lange et al. 2003; Yang et al. 2007). However, the regulatory network of MYB26 remains to be fully identified. To address this issue, the MYB26 direct targets and interactive proteins were investigated. Putative targets of MYB26 were selected, based on their expression patterns, from previously determined expression profiles of the ms35 mutant (Song, 2009). PKSP, a receptor-like cytoplasmic kinase (RLCK) was co-expressed with MYB26. Chromatin immunoprecipitation (ChIP)-PCR indicated that MYB26 may bind to the first intron of PKSP. The NAC SECONDARY WALL–PROMOTING FACTOR1 (NST1) and NST2 genes have been demonstrated as direct targets of MYB26 in ChIP-PCR. However, electrophoretic mobility shift assay (EMSA) did not show binding and retardation, possibly due to the requirement of additional proteins to facilitate MYB26 binding. MYB26 interactive proteins were investigated using the yeast two-hybrid system (C.Yang, Z.A.Wilson, unpublished data) and Förster resonance energy transfer (FRET) assays. Y2H560, a CHY-type/RING-type Zinc finger protein and Y2H320/TGA9, a bZIP transcription factor family protein interacted with MYB26 in plant cell nuclei. Y2H320/TGA9 has been shown to be functionally redundant with TGA10 in regulating anther development (Murmu et al. 2010). The tga9tga10 double mutant produced indehiscent anthers and was male sterile due to the developmental arrest of the adaxial anther lobes and abnormal tapetum and pollen development in the abaxial anther lobes. In summary, MYB26 appears to regulate endothecium development and secondary thickening formation and thus anther dehiscence probably through directly regulating the subfamily VII RLCK PKSP and the NAC transcription factors NST1, NST2 and by interacting with a CHY-type/RING-type Zinc finger protein Y2H560 and the bZIP transcription factor Y2H320/TGA9.